Empowering Malaysian Gen y and Gen Z: harnessing design thinking for fashion retail innovation and consumer engagement - Hassan, Normaziana (Universiti Teknologi MARA, Kedah, 2025)
The Malaysian fashion retail industry is undergoing a profound transformation, driven by rapid digital advancements, globalisation, and shifting consumer preferences (Tan, 2022; Lee and Teoh, 2021). Today, the industry is shaped by the demands of two key generational groups: Generation Y (Millennials) and Generation Z.